"You Pulled Me out of a Dark Well": A Case Study of a Colombian Displaced Woman Empowered Through Interpersonal Counseling (IPC). Issue 8 (28th July 2016) - Ceballos, Angela Milena Gomez; Andrade, Ana Claudia; Markowitz, Talia; Verdeli, Helen
Abstract : Interpersonal counseling (IPC), a briefer and simplified adaptation of interpersonal psychotherapy (IPT), was used with internally displaced women (IDW) in Bogotá, Colombia, an implementation study of a mental health care pathway funded by Grand Challenges Canada. Preliminary evidence suggests that IPC led to positive outcomes for IDW and may be a feasible first line treatment for displaced women with elevated symptoms of common mental disorders. The case study demonstrates the use of IPC as an intervention to treat depression, anxiety, and posttraumatic stress symptoms in one participant across 11 sessions, from the case formulation through the termination phase.